Development of an indirectly suspended droplet for the extraction of hazardous phenols from environmental aqueous samples. Issue 31 (26th July 2016) - Abdali, Sh.; Daneshfar, A.; Ghaedi, M.; Khezeli, T.
Abstract : ISDME of water-miscible organic solvents as a simple, convenient, quick, sensitive and environmentally friendly microextraction technique for simultaneous monitoring and clean-up of hydroxybenzene and dihydroxybenzene isomers in water. Abstract : Herein we describe indirectly suspended droplet microextraction (ISDME) of water-miscible organic solvents as a simple, convenient, quick, sensitive and environmentally friendly microextraction technique for simultaneous monitoring and clean-up of hydroxybenzene and dihydroxybenzene isomers in water samples. This method is a combination of directly suspended droplet microextraction (DSME) and salting-out assisted liquid/liquid extraction of water-miscible organic solvents. Briefly, in a typical experiment, a micro-drop of a water-miscible organic solvent (as an extraction solvent) was separated from aqueous solution by adding a salt. Then, the micro-drop of the extraction solvent containing the analytes is collected with a syringe and analyzed by HPLC-UV. To obtain optimum extraction performance, the effects of different variables such as the type and volume of water-miscible organic solvent, type of salt and extraction time were studied and discussed in detail. The proposed method is capable of determining four phenolic compounds over a range of 0.5–500 ng mL −1 with a limit of detection between 0.05 and 0.11 ng mL −1 . In our experiments, good linearity coefficients ( R 2 ranging from 0.9974 to 0.9991), precisions (the intra- and inter-day relative standard deviation values of the method were lower than 4.8%) and enrichment factors (EFs) of 160–186 were achieved. The method was successfully applied to the determination of phenol, catechol, resorcinol and hydroquinone in various water samples.